RASPBERRY AND PLUM –THE NATIONAL BRAND - Mihajlović, Božidar (Economics of Agriculture, 2006)
In Serbia and Montenegro has very valuable most important and export raspberry and plums, and has essence influential on the realized balance of payment of our country. Export is accelerator of the raspberry and plum production, and present imperative of future development. For this purpose raspberry and plum production and processing must be developed and modernized, following the demands, quality and standards in the world market at the same time. The existing assortment for these products is poor (IQF – frozen original, usually classic packages); on the other hand, its improvement is in progress.